Hak-Hak Pekerja terhadap Perusahaan yang Pailit Ditinjau dari Hukum Ketenaga Kerjaan di Indonesia - Feibe Angeline Pijoh; Joupy G.Z. Mambu; Yosua Laurens (Civic Education: Media Kajian Pancasila dan Kewarganegaraan, 2023)
Problems faced What are the Rights of Workers who get Unilateral Termination of Employment by the Employer/Company while the company does not have the financial capability both financially and guarantees of the value of assets owned by the Employer/Company, this type of Juridical-Normative research, This research is included in the category library research (library research), namely research that analyzes various literature and produces a conclusion. The results of the study show that the fulfillment of employee rights by employers/companies as a result of the implementation of layoffs, often cannot be fulfilled by employers/companies due to other legal interests that have been included in the company's/entrepreneur's business, as one of the company's instruments to carry out investment activities, so that the mechanism for fulfilling the rights of laid-off employees requires time and several legal processes which actually hinder the fulfillment of the rights of laid-off employees